Exploring the Antifungal Potential of Lawsone-Loaded Mesoporous Silica Nanoparticles Against Candida albicans and Candida glabrata: Growth Inhibition and Biofilm Disruption - Fatemeh Nikoomanesh; Mahsa Sedighi; Mahdi Mahmmoodi Bourang; Mitra Rafiee; André Luis Souza dos Santos; Maryam Roudbary (Journal of Fungi)
The incidence of fungal infections is significantly rising, posing a challenge due to the limited class of antifungal drugs. There is a necessity to combat emerging resistant fungal infections by developing novel antifungal agents. This study aimed to evaluate the antifungal effects of lawsone (LAW), a natural component extracted from herbal medicine, and LAW-loaded mesoporous silica nanoparticles (LAW-MSNs) on growth, biofilm formation, and expression of ALS1 and EPA1 genes contributing to cell adhesion of Candida spp. Twenty C. albicans and twenty C. glabrata isolates, including ten fluconazole-resistant and ten fluconazole-susceptible isolates, were examined. The findings of the study indicated that LAW and LAW-MSNs inhibited Candida isolates growth at MIC range of 0.31–>5 µg/mL and significantly reduced biofilm formation in C. albicans and C. glabrata. Moreover, both LAW and LAW-MSNs downregulated the expression of the adhesion genes ALS1 and EPA1 in C. albicans and C. glabrata. Based on the obtained findings, LAW emerged as a promising antifungal candidate. However, the nano-formulation (LAW-MSNs) improved its antifungal properties.